Evaluation of the Effect of Hedonic Hunger on Purchasing Behavior in Adult Individuals - BİÇER, NİHAN ÇAKIR; AKBURAK, İPEK (Acıbadem Mehmet Ali Aydınlar Üniversitesi, 2022)
Objective: The aim of this study is to evaluate the effect of individuals’ hedonic hunger status on their purchasing behaviors. Materials and Methods: This cross-sectional study was conducted with 218 individuals, 147 females and 71 males, aged 18-65 years. Questions about demographic characteristics and eating habits, Power of the Food Scale (PFS), Hedonic and Utilitarian Purchasing Behavior Scale were applied via an online questionnaire. The study protocol was approved by the Ethical Committee of the Acıbadem Mehmet Aydınlar University with the number of 2021-17/10. Results: PFS total score was determined as 3.03±0.82 in females and 2.51±0.90 in males (p<0.05). According to PFS, the frequency of hedonic hunger in females (70.7%) was higher than in males (49.3%) (p<0.05). Hedonic Consumption Behavior Scale (HCBS) total and subscale scores were higher in females than males (p<0.05). A positive correlation was found between PFS and HCBS scores in females and in males between PFS and HCBS and between PFS and Utilitarian Consumption Behaviors Scale scores (p<0.05). Conclusion: Hedonic hunger and hedonic consumption behavior frequency were found to be higher and related to each other in females. It is believed that practices aimed at raising awareness in the consumption of food and non-food products and developing utilitarian purchasing behavior will contribute to weight control and sustainability.

Amaç: Bu araştırmanın amacı, bireylerin hedonik beslenme durumlarının satın alma davranışları üzerindeki etkisini incelemektir. Gereç ve Yöntem: Kesitsel tipteki bu araştırma, 18-65 yaş arası 147 kadın ve 71 erkek olmak üzere 218 birey ile yürütülmüştür. Bireylerin demografik özellikleri, beslenme alışkanlıkları ile ilgili sorular, Besin Gücü Ölçeği (BGÖ), Hedonik ve Faydacı Satın Alma Davranışı Ölçeği çevrimiçi anket yolu ile uygulanmıştır. Araştırma protokolü, Acıbadem Mehmet Aydınlar Üniversitesi Tıbbi Araştırma Etik Kurulu tarafından (sayı no: 2021-17/10) onaylanmıştır. Bulgular: Bireylerin BGÖ toplam puanı kadınlarda 3,03±0,82, erkeklerde 2,51±0,90 olarak belirlenmiştir (p<0,05). BGÖ’e göre kadınlarda (%70,7) hedonik açlık sıklığı, erkeklerden (%49,3) yüksektir (p<0,05). Kadınların Hedonik Tüketim Davranışları Ölçeği (HTDÖ) toplam ve alt boyut puanları, erkeklerden yüksektir (p<0,05). Kadınlarda BGÖ ile HTDÖ ve erkeklerde BGÖ ile HTDÖ ve BGÖ ile Faydacı Tüketim Davranışları Ölçeği puanları arasında pozitif korelasyon saptanmıştır (p<0,05). Sonuç: Kadınlarda hedonik açlık durumunun ve hedonik satın alma davranışlarının daha fazla ve birbiri ile ilişkili olduğu belirlenmiştir. Gıda ve gıda dışı ürünlerin tüketiminde farkındalığı arttırmaya ve faydacı satın alma davranışının geliştirilmesine yönelik uygulamaların, ağırlık kontrolüne ve sürdürülebilirliğe katkı sağlayacağına inanılmaktadır.
Yetişkin Bireylerde Hedonik Açlığın Satın Alma Davranışı Üzerindeki Etkisinin Değerlendirilmesi
Keywords: Nutrition; Eating Behavior; Purchasing